Efforts of Career Women in the Indonesian Army's Kowad and Civil Servants in Maintaining Household Harmony (Study at KUDAM VI/Mulawarman, Balikpapan City) - Elma Ardelia Ailsa; Lilik Andaryuni; Akhmad Sofyan (Penerbit Hellow Pustaka, 2025)
This study examines the efforts of career women in the Indonesian Army (Kowad) and civil servants (PNS TNI AD) to maintain family harmony at Kudam VI/Mulawarman, Balikpapan. The main issue lies in the dual roles of women as wives, mothers, and professionals, which may create family conflicts. Based on family harmony theories, factors such as communication, cooperation, and emotional support from spouses are crucial for maintaining balance. This research employed a qualitative method with an empirical legal approach, using interviews and observations of career women and their families. The findings reveal that career women strive to maintain family harmony through time management, open communication, quality family time, and involving husbands in domestic tasks. Nevertheless, challenges include limited time, dual-role pressures, and psychological burdens. The study concludes that spousal support and effective communication are the main keys to achieving harmonious families, despite the dual responsibilities faced by women in both professional and domestic spheres.